2017
DOI: 10.1371/journal.pone.0176305
|View full text |Cite
|
Sign up to set email alerts
|

Nitrapyrin addition mitigates nitrous oxide emissions and raises nitrogen use efficiency in plastic-film-mulched drip-fertigated cotton field

Abstract: Nitrification inhibitors (NIs) have been used extensively to reduce nitrogen losses and increase crop nitrogen nutrition. However, information is still scant regarding the influence of NIs on nitrogen transformation, nitrous oxide (N2O) emission and nitrogen utilization in plastic-film-mulched calcareous soil under high frequency drip-fertigated condition. Therefore, a field trial was conducted to evaluate the effect of nitrapyrin (2-chloro-6-(trichloromethyl)-pyridine) on soil mineral nitrogen (N) transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Addition of nitrification and urease inhibitors with urea did not affect dry matter, yield, as well as N accumulation, allocation and NRE of cotton in this study. In the same area as in the current study, Liu et al also reported that use of a nitrification inhibitor nitrpyrin did not affect cotton yield under drip-fertigation system 14 . The ineffectiveness of inhibitors could be associated with several factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Addition of nitrification and urease inhibitors with urea did not affect dry matter, yield, as well as N accumulation, allocation and NRE of cotton in this study. In the same area as in the current study, Liu et al also reported that use of a nitrification inhibitor nitrpyrin did not affect cotton yield under drip-fertigation system 14 . The ineffectiveness of inhibitors could be associated with several factors.…”
Section: Discussionsupporting
confidence: 61%
“…A few studies have investigated the effect of urease and nitrification inhibitors on productivity and NUE of cotton under the drip-fertigated cropping system. For example, in the same area as in the current study, Liu et al found that use of a nitrification inhibitor nitrpyrin did not affect yield but increased NUE of cotton under drip-fertigation system 14 . For irrigated corn in Spain, use of a new nitrification inhibitor DMPSA and drip-fertigation did not affect N uptake or yield but reduced N losses through N 2 O emissions, compared with the conventional system (sprinkler irrigation without inhibitors) 15 .…”
supporting
confidence: 50%
“…A negative exponential relationship of soil pH with N 2 O emissions was observed (Van den Heuvel et al, 2011). Early‐growing‐season flux of N 2 O observed in the DB+NI treatment suggested that NI lowered early soil NO 3 − concentrations or greater plant uptake occurred during the early and mid‐growing season, which decreased the concentration of NO 3 − substrate available for denitrification (Liu et al, 2017; Wolt, 2004). However, the late growing season peak in N 2 O flux in the DB+NI treatment could be explained by the short‐lived impact of NI or due to lower soil pH of the subsoil resulting in higher emissions of N 2 O (Johnson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The total nitrogen (TN) content was determined by the Kjeldahl method (Bremner, 1960). Ammonium nitrogen (AN) and nitrate nitrogen (NN) were determined with an AA3 continuous flow analytical system (Seal, German) (Liu, Liang, & Chu, 2017). The total phosphorus (TP) was determined by the perchloric acid-concentrated sulfuric acid digestion and the Mo-Sb colorimetric method (Kuo, 1996).…”
Section: Soil Characteristicsmentioning
confidence: 99%